Public Speaking Training and Assistance – Master of Ceremony – for Cadres of Special Branch Leaders of 'Aisyiyah Malaysia (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Public Speaking training and assistance, especially for the role of Master of Ceremony (MC), is very important for Aisyiyah cadres of the Aisyiyah Special Branch Leadership of Aisyiyah Malaysia. The purpose of the training is to improve communication skills, increase confidence, manage events well, improve professionalism, convey organizational messages, build collaboration, and develop leadership. This service was carried out in a hybrid manner by carrying out 3 meetings using the Zoom Meeting platform and 2 days of mentoring to become an MC which was carried out directly in Kuala Lumpur, Malaysia. The output of this service is the MC videos of the trainees uploaded on social media, as well as news on national media in Indonesia and other media in Malaysia. In addition, the mechanism for the implementation of this training and mentoring will be published in the National Community Service Journal and recorded in the Intellectual Property Rights whose purpose is to create standards for public speaking training and assistance, especially MC’s for ‘Aisyiyah cadres in the Aisyiyah Special Branch Leadership abroad.